Astrophysics at ultra-high energies : International School of Cosmic Ray Astrophysics, 15th course, Erice, Italy, 20-27 June 2006 - Shapiro, Maurice M. (Maurice Mandel), 1915-; Stanev, Todor; Wefel, J. P. (World Scientific, 2007)
This book introduces young researchers to the exciting field of ultra-high energy astrophysics including charged particles, gamma rays and neutrinos. At ultra-high energy the radiation is produced by interactions of cosmic ray particles accelerated in explosive events such as supernovae or hypernovae, black holes or, possibly, the big bang. Through direct contact with senior scientists, now actively planning the next generation of experiments/models, the excitement and motivation for research at ultra-high energy was conveyed. The underpinning of these fields is a synthesis of knowledge and t.
Keywords: Cosmic rays -- Congresses.; Nuclear astrophysics -- Congresses.; Gamma rays -- Congresses.; Rayonnement cosmique -- Congrès.; Astrophysique nucléaire -- Congrès.; Rayons gamma -- Congrès.; SCIENCE -- Physics -- Astrophysics.; Cosmic rays; Gamma rays; Nuclear astrophysics; Conference papers and proceedings